Role of Lifestyle Modification in the Prevention of Atherosclerosis - Habib Khan, Farida; Khalid, Ghosoun; Al-dhairi, Ghadametab (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Literature has shown that globally the incidence of atherosclerosis is increasing every year, which is an alarming situation. Atherosclerosis affects all arteries in the body, especially the arteries in the heart, brain, and kidneys. Diseases secondary to atherosclerosis are the leading cause of death. Management for atherosclerosis includes lifestyle changes, medicine, and surgery. Fortunately, most people can prevent or delay the initiation and progression of atherosclerosis by lifestyle modifications, such as maintaining a healthy diet, engaging in regular physical activity, getting adequate sleep, and managing smoking and stress. Aim: To assess the level of awareness of Saudi community regarding the risk factors for atherosclerosis. Methods: Study design was analytical cross-sectional. Inclusion criteria was all residents of Saudi Arabia above the age of 18 years while exclusion criteria were those who belonged to medical background as their preexisting knowledge could confound the results. Sample size was 542. Data was collected by a structured questionnaire. The questionnaire was fed on Google Form and the link was sent to participants on Wattsapp. Non-probability convenience sampling technique was adopted. Results: Results revealed that despite knowing that obesity (76%) and physical inactivity (66%) are risk factors for atherosclerosis, the overall study participants were overweight. Fifty percent did not do any sort of exercise. Dietary history revealed that the majority of the respondents (54%) consumed red meat and dairy products. Forty-two percent consumed fried items. Consumption of olive oil, fish oil, fruits, and vegetables was very low (<20%).The majority did not screen themselves for atherosclerosis (99%), cholesterol levels (95%), and blood pressure (92%). Conclusions: Modifiable risk factors in prevention of atherosclerosis were poor diet quality, smoking, obesity and sedentarism. Majority of study populations did not know their cholesterol profile and blood pressure level due to lack of awareness.